Urban discourse: textualities and materialities - doi: 10.4025/actascilangcult.v35i2.17277 - Venturini, Maria Cleci (Acta Scientiarum. Language and Culture, 2012)
The constitution of the urban discourse is herein understood taking into account the central ideas of the place of memory and the foundational discourses. The discussion is focused on the two notions related to the maintenance effect, which is the product of the memory and the return of the discourses that sustain the present discourses. The relation between places of memory and foundational discourses is demonstrated by the analysis of two texts that comprise the discourse concerning Erico Verissimo in Cruz Alta, Rio Grande do Sul State, Brazil.